2014
DOI: 10.1002/app.40414
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and thermal properties of polylactide/palygorskite composites

Abstract: Polylactide palygorskite (fibrous clay) composites were prepared by solvent casting method. Both pristine and organically modified palygorskite were used for composite preparation. The detailed crystallization behavior, morphology, and thermal properties of neat polylactide and the corresponding composites were investigated by using differential scanning calorimetry, polarized optical microscopy, scanning electron microscopy and wide angle X‐ray diffraction techniques. The results showed that the crystallizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Pillai et al [ 51 ] prepared PLA/Paly nanocomposites by solvent casting in chloroform. Both pristine and organically modified palygorskite (Org‐paly) (prepared by cation exchange reaction between Paly with a quaternary ammonium salt di (hydrogenated tallow) dimethyl ammonium chloride) were used for nanocomposite preparation.…”
Section: Processing and Characterization Of Pla Nanocompositesmentioning
confidence: 99%
See 3 more Smart Citations
“…Pillai et al [ 51 ] prepared PLA/Paly nanocomposites by solvent casting in chloroform. Both pristine and organically modified palygorskite (Org‐paly) (prepared by cation exchange reaction between Paly with a quaternary ammonium salt di (hydrogenated tallow) dimethyl ammonium chloride) were used for nanocomposite preparation.…”
Section: Processing and Characterization Of Pla Nanocompositesmentioning
confidence: 99%
“…Among the nanofillers, nanoclays are the oldest and have attracted maximum interest among researchers [41] because of the significant enhancement in mechanical, barrier, and flame resistance properties, as well as accelerated biodegradation, which they help to achieve. [10,13] Though organically modified layered silicates (OMLS) are the most widely used clays, [3,[42][43][44][45][46] use of other clays with different morphologies, such as halloysite nanotubes (Hal or HNT), [24,47,48] sepiolite (a fibrous silicate having microporous channels running along the length of the fibers), [49,50] and palygorskite (Paly) (a fibrous silicate having needle like morphology) [51] has also been reported in literature. Due to its recyclability, anisotropic shape, biocompatibility, adjustable surface chemistry and the ability to impart superior, thermal, mechanical, and barrier properties, nanocellulose is another filler, which has gained significant interest in research on PLA-based nanocomposite.…”
Section: Nanoparticles Used For the Development Of Pla-based Nanocomentioning
confidence: 99%
See 2 more Smart Citations
“…This process is diffusion-controlled and requires long residence times under the pressure buildup, occurring inside the extruder; the drawback is that high residence times or high screw speeds may lead to polymer degradation, especially with polymers having low thermal stability, such as PLA [13,14]. Moreover, it has been found that clay exfoliation may not be a sufficient condition to obtain optimum properties; clay platelets dispersion and polymer-clay interaction need to be also taken into consideration to produce high performance nanocomposites [15][16][17]. Also nanosilica has been largely used to improve the properties of polymers such as PLA, to control rheological behavior or as a structural reinforcement [18][19][20]; as reported for clay particles, also with nanosilica it is important to obtain a very good dispersion of the mineral in the polymer matrix.…”
Section: Introductionmentioning
confidence: 97%